A fitness assessment study among young fishermen of coastal areas of East Midnapore District of West Bengal, India - Sengupta, Pallav; Sahoo, Sobhana (South East Asia Journal of Public Health, 2013)
Being the fourth most populated state of India, West Bengal has a population of about 82 million, of which a major percentage is represented by coastal fishing communities who are habituated to do a physically demanding occupation which may have a positive influence on their the physical parameters. Thus the present investigation was designed in order to assess the influence of fishery, such a physically demanding occupation on physical fitness and to compare whether fishermen have more cardiovascular fitness and anaerobic power than sedentary workers or not. The study was conducted in 15 randomly selected male fishermen of the Midnapore District (East), West Bengal, India (mean age of 22.5), and the 15 college students (mean age of 21.9) served as a control group. A significant difference (p<0.05) in blood pressure, PFI, energy expenditure, body fat% and anaerobic power was found in fishermen. But, in contrast, BSA, BMI, resting heart rate, VO2max, mean upper arm circumference, thigh and calf circumferences were found to be non-significant. This study implies fishermen have more physical fitness (cardiovascular fitness) and muscle mass, but a lower percentage of body fat than the sedentary population. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13210 South East Asia Journal of Public Health 2011:1:28-34